2019
DOI: 10.1111/echo.14568
|View full text |Cite
|
Sign up to set email alerts
|

Early left atrial dysfunction is associated with suboptimal cardiovascular health

Abstract: Aims: Two-dimensional speckle-tracking echocardiography can assess left atrial (LA) function by measuring atrial volumes and deformation parameters (strain, strain rate). This cross-sectional analysis explores the association between ideal CV health (CVH), LA function, and systemic biomarkers in healthy individuals from the Chilean MAUCO Cohort. Methods:We enrolled 95 MAUCO participants with different levels of CVH (mean age: 51 ± 8 years). We categorized participants into low or high CVH groups: A: 0-2, or B:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…For instance, a study from the University of Oxford which enrolled 4,344 UKPDS participants discovered that a doubled HOMA2-IR value in newly diagnosed T2DM patients was associated with a 5% greater risk of HF death and a 14% greater risk of HF onset over a median follow-up of 16.4 years [ 17 ]. Apart from overt HF, the predictive value of IR for subclinical cardiac adverse remodeling has also been proposed [ 19 21 ]. A prospective study evaluated multilayer global longitudinal strain (MGLS) of matched patients with or without IR and concluded that patients with higher HOMA-IR values had significantly lower strain values [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study from the University of Oxford which enrolled 4,344 UKPDS participants discovered that a doubled HOMA2-IR value in newly diagnosed T2DM patients was associated with a 5% greater risk of HF death and a 14% greater risk of HF onset over a median follow-up of 16.4 years [ 17 ]. Apart from overt HF, the predictive value of IR for subclinical cardiac adverse remodeling has also been proposed [ 19 21 ]. A prospective study evaluated multilayer global longitudinal strain (MGLS) of matched patients with or without IR and concluded that patients with higher HOMA-IR values had significantly lower strain values [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results obtained with this method may be affected by age, heart rate, preload and afterload. Additionally, these parameters do not fully reflect the expansion of the myocardium in the middle and late diastole 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these parameters do not fully reflect the expansion of the myocardium in the middle and late diastole. [10][11][12] Speckle tracking echocardiography (STE) shows the time-LAV curves in detail, evaluating the phasic LAV and LA functions over time.…”
Section: Introductionmentioning
confidence: 99%